PENGARUH ISLAMIC BRANDING, LABEL HALAL, LABEL BPOM, TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN DAN KOSMETIK: (Studi Pada Santriwati Pondok Pesantren Salafiyah Darussalam Martapura) - Malihah, Lola; Azizah, Azizah; Karimah, Husna (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2023)
This research is based on the development of various product innovations that produce various types of products, especially food and cosmetics to be consumed. Therefore, this study aims to determine the influence of  Islamic branding, the halal logo, and the BPOM logo on purchasing decisions for food and cosmetic products at the Salafiyah Darussalam Martapura Islamic Boarding School. The research method uses a quantitative approach with multiple linear regression. The population in this study was 209 Madrasah Aliyah students of X, XI, and XII levels. Then the number of samples was 140 people using purposive sampling techniques. The results showed that Islamic branding and halal logos have a positive but insignificant effect on the decision to buy food and cosmetic products, with significant levels of 0.56>0.05 and 0.49>0.05 respectively. Unlike the other two independent variables, the BPOM logo variable has a positive (0.681) and significant (0.000<0.05) effect on determining the decision to buy a product. While simultaneous effect showed that the three variables, namely the Islamic branding, halal logo, and BPOM logo had a simultaneous effect on the independent variable with a significant level of 0.000 < 0.05 with a value of Fstat = 13.515.